Oil Price Shocks and Monetary Policy in an Asymmetric Monetary Union - Hans-Werner Wohltmann; Volker Clausen (Kiel University, Department of Economics, 2003)
This paper analyzes the dynamic effects of anticipated and unanticipated oil price increases in a small two-country monetary union, which is simultaneously characterized by asymmetric wage adjustments and asymmetric interest rate sensitivities of private absorption. It is shown that both types of oil price disturbances lead to temporary divergences in output developments across the monetary union. In the case of anticipated oil price increases the relative cyclical position of output effects is reversed in the course of the adjustment process. With anticipated oil price increases complete stabilization of the output variables throughout the overall adjustment process requires restrictive monetary policy to be time-inconsistent from a quantitative but time-consistent from a qualitative point of view. That means that the central bank credibly announces a future reduction in the growth rate of nominal money stock but actually realizes a decrease in the monetary growth rate, which is less restrictive than the announcement.
urn:nbn:de:101:1-20091110480
Keywords: E63; F41; 330; EMU; international policy transmission; oil price shock; time inconsistency; Mineralölpreisschock; Geldpolitik; Währungsunion; Zwei-Länder-Modell; Konjunkturzusammenhang; Zeitkonsistenz; Theorie